Current understanding and management of giant cell arteritis and polymyalgia rheumatica. (November 2010) - Ghosh, Parasar; Borg, Frances A; Dasgupta, Bhaskar
Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are linked conditions that occur in the elderly. GCA is a vasculitis of large- and medium-sized vessels causing critical ischemia. It is a medical emergency owing to the high incidence of neuro-ophthalmic complications. PMR is an inflammatory disease characterized by abrupt-onset pain and stiffness of the shoulder and pelvic girdle muscles. Both conditions are associated with a systemic inflammatory response and constitutional symptoms. The pathogeneses are unclear. The initiating step may be the recognition of an infectious agent by activated dendritic cells. The key cell type involved is CD4 + T cells and the key cytokines are IFN-γ (implicated in granuloma formation) and IL-6 (key to the systemic response). The pathogenesis of PMR may be similar to that of GCA, however, PMR exhibits less clinical vascular involvement. The mainstay of therapy is corticosteroids, and disease-modifying therapy is indicated in relapsing disease. This article reviews recent guidelines on early recognition, investigations and management of these diseases, as well as advances in imaging.